Characterizing the demographic history and prion protein variation to infer susceptibility to chronic wasting disease in a naïve population of white‐tailed deer (Odocoileus virginianus). (30th March 2021) - Haworth, Sarah E.; Nituch, Larissa; Northrup, Joseph M.; Shafer, Aaron B. A.
Abstract: Assessments of the adaptive potential in natural populations are essential for understanding and predicting responses to environmental stressors like climate change and infectious disease. Species face a range of stressors in human‐dominated landscapes, often with contrasting effects. White‐tailed deer ( Odocoileus virginianus ; deer) are expanding in the northern part of their range following decreasing winter severity and increasing forage availability. Chronic wasting disease (CWD), a prion disease affecting deer, is likewise expanding and represents a major threat to deer and other cervids. We obtained tissue samples from free‐ranging deer across their native range in Ontario, Canada, which has yet to detect CWD in wild populations. We used high‐throughput sequencing to assess neutral genomic variation and variation in the prion protein gene (PRNP) that is partly responsible for the protein misfolding when deer contract CWD. Neutral variation revealed a high number of rare alleles and no population structure, and demographic models suggested a rapid historical population expansion. Allele frequencies of PRNP variants associated with CWD susceptibility and disease progression were evenly distributed across the landscape and consistent with deer populations not infected with CWD. We estimated the selection coefficient of CWD, with simulations showing an observable and rapid shift in PRNP allele frequencies that coincides with the start of a novel CWD outbreak. Sustained surveillance of genomic and PRNP variation can be a useful tool for guiding management practices, which is especially important for CWD‐free regions where deer are managed for ecological and economic benefits.